2018
DOI: 10.1590/1807-1929/agriambi.v22n2p119-124
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gas exchanges of arugula plants under silicon fertilization and water restriction

Abstract: A B S T R A C TThe objective of this article was to study the growth and gas exchange of arugula plants under silicon (Si) fertilization and water stress. The experiment was installed in a greenhouse, located in the municipality of Pombal, PB, Brazil, whose geographic coordinates are 6º 46 'S latitude and 37º 49' W longitude and 178 m of altitude, situated in the 'Sertão Paraibano' micro-region. The experimental design was in randomized blocks, in 5 x 2 factorial scheme, corresponding to five Si doses (0, 50, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
3
10
0
3
Order By: Relevance
“…At 60 DAI there was an increase up to the dose of 9.08 mL L -1 , decreasing in subsequent doses ( Figure 3C). The results obtained in the present study corroborate those observed by Jesus et al (2018) in arugula, when they found that the application of silicon increased the rate of transpiration.…”
Section: Resultssupporting
confidence: 92%
“…At 60 DAI there was an increase up to the dose of 9.08 mL L -1 , decreasing in subsequent doses ( Figure 3C). The results obtained in the present study corroborate those observed by Jesus et al (2018) in arugula, when they found that the application of silicon increased the rate of transpiration.…”
Section: Resultssupporting
confidence: 92%
“…for the fresh and dry mass of the stem, reaching reductions of 59.8 and 97.1%. These results indicate that the application of Si promotes the development in plants under water deficit in function of promoting improvements in nutritional balance, providing a greater accumulation of Si in the cell wall and favoring the accumulation of biomass [28,12].…”
Section: Resultsmentioning
confidence: 81%
“…This effect suggests that decreasing water availability reduces leaf emission and mass production. Thus, the Si applied to plants with low water availability promotes improvements due to the deposition of Si in the roots, leaves and stem, reducing water loss through transpiration [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para tanto, determinou-se o peso dos vasos na capacidade de campo (P cc ) a partir da saturação por capilaridade, seguida de drenagem até peso constante, sendo considerado o P cc , e diariamente procedia-se à pesagem do peso atual (P a ) de cada vaso. Com esses dados e usando-se a equação 1, determinou-se a ETr com a divisão da subtração desses valores pela área do vaso (JESUS et al, 2018). As plantas que recebiam 50% da ETr recebiam 50% do volume de água aplicado nas plantas sob lâmina de 100% da ETr.…”
Section: Methodsunclassified